Teachers' voices and quality education in the basic education discourse in South Africa - Samantha Hoffman; Rouaan Maarman (Perspectives in Education)
The absence of a shared understanding of quality education for South African schools prompted this study to apply the capability approach of Amartya Sen to investigate the productive qualities of teachers. The study outlines the significance of integrating teachers’ perspectives into discussions surrounding quality education in South Africa. More emphasis is directed towards the necessity of understanding quality education through the lens of teachers’ experiences and perceptions. A case study design was used and teachers in two Cape Town schools were selected to illustrate the case. The study conducted in-depth individual and focus group interviews with primary and high school teachers to explore their views on quality education and its implications for capability enhancement. Utilizing the capability approach as a framework, the research underscores the voices of teachers and the pivotal role of teachers in shaping educational practices and policies. The study revealed that limitations put on teachers’ voices rendered the understanding of quality education a bureaucratic discourse instead of a transformational idea and suppresses evaluative reasoning and the pursuit of interconnected teaching and learning freedoms in schools.